Quantification of Seventeen Phenolic Acids in Non-Soy Tempeh Alternatives Based on Legumes, Pseudocereals, and Cereals - Miloslav Šulc; Jana Rysová (Foods, 2025)
The rising demand for sustainable and health-promoting foods has encouraged the development of tempeh from non-soy plant materials. This study investigated tempeh alternatives made from sorghum, proso millet, white bean, buckwheat, yellow pea, and quinoa, focusing on their phenolic acid (PA) content. Seventeen PAs and two flavan-3-ols were quantified using LC-MS/MS in free, conjugated, and insoluble forms, and total phenolic content (TPC) was determined using the Folin–Ciocalteu assay. Four PAs—shikimic acid, 3-hydroxycinnamic acid, 3,5-dihydroxybenzoic acid, and 2-hydroxycinnamic acid—were not detected. Solid-state fermentation increased the total PA (TPA) content by an average of 11.3%, reaching 160.6 µg/g, with the most significant rise in conjugated and insoluble fractions. The highest TPA values were observed in sorghum-based tempeh, particularly quinoa:sorghum (2:1; 293 µg/g), sorghum:yellow pea (2:1; 277.6 µg/g), and buckwheat:sorghum (1:1; 271 µg/g). The most abundant PAs were ferulic (18 µg/g), vanillic (14.6 µg/g), 3,4-dihydroxybenzoic (8 µg/g), and caffeic acids (6.7 µg/g). TPC values reached up to 9.51 mg GAE/g in tempeh samples. These findings support the use of non-soy substrates to develop nutritious, allergen-free, gluten-free tempeh products with enhanced phenolic profiles and functional food potential.